Can Postoperative CT Imaging in Spine Surgery Be Replaced by Intraoperative 3D Rotation With the C-Arm?: Results of a Prospective Single Center Cohort Study - Banat, Mohammed; Wach, Johannes; Salemdawod, Abdallah; Domurath, Lisa; Scorzin, Jasmin; Vatter, Hartmut (Frontiers in Surgery, 2021)
Objective Spinal dorsal instrumentation is an established treatment option for a range of spinal disorders. Intraoperative fluoroscopy in combination with navigation reduce the risk of incorrect screws placement. In several cases, postoperative CT scans are needed to verify possible mismatches. In this study, we evaluated the efficacy of 3 D intraoperative fluoroscopy as compared to postoperative CT and the need of postoperative CT. Methods In this prospective single-center study 94 patients were included. Intraoperative images were acquired using a 3D C-arm with a navigation system. The final position of the screws was verified by a postoperative CT scan. Finally, we compared mismatches between intraoperative and postoperative CT imaging results using Rampersaud-grade (A-D) Results 607 screws in 94 patients were included. All of the screws were implanted using the navigation and 3D C-arm. Some 3% of the screws had to be replaced directly intraoperative due to inadequate positioning with median or lateral breaches. An A-score was achieved for 85.5% of the 3D controlled screws and 87% of the postoperative CT. A B-score was found in 11.5% of both groups. In the 3D group a C-score was achieved for 2.5% and in the CT group for 0.8%. A D-score was found in 0.5% of the screws in both groups, p=0.45. Only a mismatch of 3% could be detected for the intraoperative and postoperative imaging results. Conclusion Our study shows that the placement of screws using a 3D tool is accurate. There were no relevant mismatches between intraoperative images and the postoperative CT.